STRATEGI PENGEMBANGAN BISNIS PRODUK BAWANG GORENG DI INDUSTRI KECIL MENENGAH (IKM) RAJA BAWANG DI MASA PANDEMI COVID-19 - Afrini; Alam, Max Nur; Christoporus; NurT, Fanny Iswarini NurT; Arfanika, Ici (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
Raja Bawang Small and Medium Industries (SMI) is one of the fried onion processing industries that has survived in the midst of the COVID-19 pandemic in Palu City. This study aims to see how the marketing strategy of Raja Bawang SMI in the midst of the covid-19 pandemic. This study uses primary data obtained through direct interviews with 5 respondents at the research site. The analytical tool used in this research is SWOT analysis. Based on the calculations, it was found that the total value of IFAS was 1.31 and the total value of EFAS was 2.82. Thus the marketing strategy of the Raja Bawang IKM during the Covid-19 pandemic is in Quadrant II. Thus the IE matrix for Raja Bawang SMEs is in a position of growth and stability. The results of determining the strategy are the first to do promotions, by doing promotions to consumers online, for example on the various kinds of social media available, the second to choose a strategic location, choose a strategic location that is easily accessible by customers, since the corona IKM Raja Bawang has chosen to market its products in all Alfamidi Outlets around Palu City and the third Using Internet marketing, one of the marketing strategies that is widely used by entrepreneurs is internet marketing